ALLERGIC REACTIONS TO LATEX IN CONDITIONS OF THE COVID-19 PANDEMIC - Abdullaeva Dilafruz Gayratovna; Abdullaev Mansur Abdusattarovich; Iskandarova Gulnoza Tulkinovna (Galaxy International Interdisciplinary Research Journal, 2022)
The purpose of the study is to examine country-specific important allergens, identify hidden allergens, and interpret MDA results to diagnose Type I allergic reactions.